Stability issues in Kaleckian models driven by autonomous demand growth: Harrodian instability and debt dynamics - Eckhard Hein; Ryan Woodgate (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2020)
Sraffian supermultiplier models, as well as Kaleckian distribution and growth models making use of non-capacity creating autonomous demand growth in order to cope with Harrodian instability, have paid little attention to the financial side of autonomous demand growth as the driver of the system. Therefore, we link the issue of Harrodian instability in Kaleckian models driven by non-capacity creating autonomous demand growth with the associated financial dynamics. For a simple model with autonomous government expenditure growth, zero interest rates and no consumption out of wealth, we find that adding debt dynamics does not change the results obtained by Lavoie (2016) for a model without debt, i.e. the long-run equilibrium is stable if Harrodian instability is not too strong and the autonomous growth rate does not exceed a maximum given by the long-run equilibrium saving rate. Introducing interest payments on government debt as well as consumption out of wealth into the model, however, changes the stability requirements: First, the autonomous growth rate of government expenditures should not fall short of the exogenous monetary interest rate. Second, this growth rate should not exceed a maximum given by the saving rate in long-run equilibrium minus the propensity to consume out of wealth. Third, Harrodian instability may be stronger than in the simple model without violating long-run overall stability, in particular, if the rate of interest is very low and the growth rate of government expenditures is close to the mentioned upper limit. We claim that, irrespective of the relevance or irrelevance of Harrodian instability, it is necessary to introduce financial variables into models driven by non-capacity creating autonomous demand in order to assess the long-run (in-)stability and sustainability of growth.
Keywords: E11; E12; E25; E62; 330; Supermultiplier; autonomous demand growth; Kaleckian models; Harrodian instability; financial (in)stability